DECISION USEFULNESS: DALAM PENGAMBILAN KEPUTUSAN DAN INVESTASI - Fahrudin A, Ahmad (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
This paper discusses the financial report based on historical prices. Using historical price makes it useful even today emerged another method. To quickly understand this concept, we need to consider other theories of the economics and finance. As an accountant, you can not begin to make financial statements more useful to us to know what is meant by usefulness. We also need a proper description of the information. Decision theory and the theory of investment helps in understanding the concepts of financial reporting information. Â